2022
DOI: 10.3389/fsurg.2022.939857
|View full text |Cite
|
Sign up to set email alerts
|

The serial changes of Neutrophile-Lymphocyte Ratio and correlation to weight loss after Laparoscopic Sleeve Gastrectomy

Abstract: PurposeThis study aims to identify the pre- and postoperative changes in the neutrophil-lymphocyte ratio (NLR) and its correlations to clinical characteristics in obese patients who underwent laparoscopic sleeve gastrectomy (LSG).MethodRetrospectively, we included patients who has undergone LSG in our institution between January 2019 and April 2021. A total of 100 patients whose body mass index over 32.5 and received primary laparoscopic sleeve gastrectomy without infectious condition were included.ResultsTher… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 54 publications
0
0
1
Order By: Relevance
“…Having in mind the link between obesity and inflammation the next logical step was to find out if the above-mentioned inflammatory markers may be used as predictors for weight loss after surgery. In a recent paper Chi PJ et al, analyzing 100 patients submitted to LSG, showed that NLR, neutrophil and lymphocyte counts significantly declined at 3-and 6-month follow-up, concluding that NLR has the potential to be used as a biomarker for weight loss after LSG [29]. We did not find such a direct correlation in our cohort.…”
Section: Discussioncontrasting
confidence: 68%
“…Having in mind the link between obesity and inflammation the next logical step was to find out if the above-mentioned inflammatory markers may be used as predictors for weight loss after surgery. In a recent paper Chi PJ et al, analyzing 100 patients submitted to LSG, showed that NLR, neutrophil and lymphocyte counts significantly declined at 3-and 6-month follow-up, concluding that NLR has the potential to be used as a biomarker for weight loss after LSG [29]. We did not find such a direct correlation in our cohort.…”
Section: Discussioncontrasting
confidence: 68%